A Data-driven Framework to Support Team Formation in Software Projects - Cunha, Felipe; Rique, Thiago; Perkusich, Mirko; Gorgônio, Kyller; Almeida, Hyggo; Perkusich, Angelo (Anais do Workshop Brasileiro de Engenharia de Software Inteligente (ISE), 2022)
Context Software analytics approaches have supported managers in making informed decisions regarding several software engineering problems. Team formation is a challenging one, being investigated by the research community as new approaches and tools have been proposed. However, the existing studies do not appropriately address the aspects and procedures to be adopted in the development of tools to meet most scenarios, besides not providing a concrete solution useful from a practical perspective. Aims This study provides a framework to support the development of solutions that can help managers form software teams. Method We interviewed a key practitioner from a software organization and analyzed the collected data to understand how the team formation problem is currently handled, identifying underlying aspects and challenges faced by the organization. Results We presented an overview of the proposed framework and the results of a preliminary evaluation performed by integrating a prototype into an enterprise system. Conclusions Our results provide a concrete solution for the team formation problem that can be integrated not only into a project management tool, but also into software analytics tools.